2009
DOI: 10.1128/jb.00767-08
|View full text |Cite
|
Sign up to set email alerts
|

Glucose- and Glucokinase-ControlledmalGene Expression inEscherichia coli

Abstract: MalT is the central transcriptional activator of all mal genes in Escherichia coli. Its activity is controlled by the inducer maltotriose. It can be inhibited by the interaction with certain proteins, and its expression can be controlled. We report here a novel aspect of mal gene regulation: the effect of cytoplasmic glucose and glucokinase (Glk) on the activity and the expression of MalT. Amylomaltase (MalQ) is essential for the metabolism of maltose. It forms maltodextrins and glucose from maltose or maltode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 60 publications
0
25
2
Order By: Relevance
“…Early work on the MalQ reaction using purified maltose as substrate demonstrated a considerable lag phase that led to the conclusion that maltotriose is the shortest possible donor (12), an observation that was not confirmed by others (6,8). Likewise, such a lag phase was not observed in our enzyme assay.…”
Section: Comparison Of the Crystal Structures Of Malq In Three Differcontrasting
confidence: 58%
See 1 more Smart Citation
“…Early work on the MalQ reaction using purified maltose as substrate demonstrated a considerable lag phase that led to the conclusion that maltotriose is the shortest possible donor (12), an observation that was not confirmed by others (6,8). Likewise, such a lag phase was not observed in our enzyme assay.…”
Section: Comparison Of the Crystal Structures Of Malq In Three Differcontrasting
confidence: 58%
“…Both are subsequently converted to glucose-6-P by glucokinase and phosphoglucomutase, respectively, to enter glycolysis. Previous investigations indicated that increased internal glucose levels reduce the activity of MalQ (8). Furthermore, maltodextrin metabolism is linked to that of glycogen via the shared intermediate maltotriose, which is not only a substrate of MalQ but also constitutes the inducer of the maltose system (9,10).…”
mentioning
confidence: 99%
“…Glucose also acts as an acceptor limiting the extent of polymerization and in increasing concentration becomes a feedback inhibitor of MalQ. The removal of glucose from the reaction mixture, for instance, by ATP and glucokinase (to form glucose-6-P that is not part of the equilibrium), allows the formation of maltodextrins of continually increasing chain length (26). This situation mimics the cytosol of a ⌬malP strain grown on maltose, where the maltodextrins formed by the MalQ activity are not reduced in size by the missing MalP enzyme.…”
Section: Vol 193 2011 Maltose Enzymes In Glycogen Synthesis By E Cmentioning
confidence: 99%
“…It is possible that the filamentation and cell death in dGTP-starved cultures release maltodextrins into the medium. Alternatively, maltotriose can be generated from endogenous sources, such as glycogen (46) or trehalose (47), or by factors associated with the accumulation of unphosphorylated glucose (48). For example, during unbalanced growth, the flow of carbon in and out of the glycogen reservoir may be altered, leading to upregulated maltotriose levels, as could be the upregulation of trehalose import (treB; 3.1-fold) ( Table 4).…”
Section: Figmentioning
confidence: 99%